Hybrid Solutions for the Surgical Treatment of Multilevel Degenerative Cervical Disk Disease - König, Stefan Alexander; Ranguis, Sebastian; Spetzger, Uwe (The Surgery Journal, 2015)
Background In different stages of cervical degenerative disk disease, the combination of dynamic and nondynamic implants may be considered. The aim of this study was to investigate the applicability of criteria to assist decision making in these cases.Methods Thirty patients with spondylotic cervical radiculopathy and a coincidence of soft disk and hard disk herniation were surgically treated with a hybrid solution (combination of total disk replacement and cage fusion). The control group included 32 patients who underwent two-level cage fusion. Pre- and postoperative Japanese Orthopaedic Association (JOA) scores and range of motion (ROM) were compared.Results Twenty-three patients underwent two-level hybrid solution and 7 underwent three-level treatment. The most frequent solution (n = 13) was a combination of a dynamic implant at C5–C6 and a nondynamic implant at C6–C7. The mean JOA score improved from 13.9 to 15.6 points after surgery (mean deviation [MD] 1.6, 95% confidence interval [CI] 2.1 to 1.2, p < 0.001). ROM showed a slight trend to increase (MD 0.8, 95% CI −0.9 to 2.6, p = 0.193). In the control group, the mean JOA score improved from 13.3 to 15.1 points after surgery (MD 1.4, 95% CI 2.1 to 1.2, p < 0.001). The comparison of the postoperative JOA scores and recovery rates between the hybrid treatment group and the control group did not show significant differences.Conclusions In cases of coincident soft and hard degenerative cervical disk disease at adjacent levels, the combination of a disk prosthesis and a nondynamic implant is a safe and effective treatment option and an alternative to multilevel fusion.
Keywords: cervical spine; degeneration; fusion; disk replacement; hybrid surgery